KELAS KLINIK BERBASIS MULTIPLE INTELEGENCES SEBAGAI SOLUSI PEMILIHAN JURUSAN KULIAH DAN KARIR - Oktaffi Arinna Manasikana; Andhika Mayasari; Ita Rahmania Kusumawati; M. Bambang Edi Siswanto; Lina Arifah Fitriyah; Noer Af’idah, (Prosiding Seminar Nasional Sains, Teknologi, Ekonomi, Pendidikan dan Keagamaan (SAINSTEKNOPAK), 2021)
Abstract: Class 12 is the decision to choose a major in a university that will support his career in the future. From the results of interviews with teachers of MA Midanutta'lim Jogoroto Jombang, graduates in 2020 around 55% continue their studies to college and 45% go straight to work. 12th graders have difficulty choosing college majors and career places for those who work, partly because they do not know their talents and interests, especially developing these talents and interests. The service that is done to the 12th grade students of MA Midanutta'lim Jogoroto Jombang is to create a clinical class in collaboration with the BK teacher. The clinical class went through several stages: (1) Conducting training and mentoring for students in finding talents and interests; (2) Conduct training and mentoring for students in finding appropriate multiple intelligences based on Multiple Intelligences; (3) Provide assistance to parents and students to determine college majors; (4) and direct the right career.